2023
DOI: 10.1002/ctm2.1243
|View full text |Cite
|
Sign up to set email alerts
|

The clinical potential of optogenetic interrogation of pathogenesis

Abstract: Background Opsin‐based optogenetics has emerged as a powerful biomedical tool using light to control protein conformation. Such capacity has been initially demonstrated to control ion flow across the cell membrane, enabling precise control of action potential in excitable cells such as neurons or muscle cells. Further advancement in optogenetics incorporates a greater variety of photoactivatable proteins and results in flexible control of biological processes, such as gene expression and signal tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 112 publications
0
1
0
Order By: Relevance
“… 51 The process involves introducing the components of the photocontrol system or cells containing the therapeutic gene into the human body and using light to induce the degradation of the target gene at the transcriptional and protein levels, thereby achieving a therapeutic effect. 52 , 53 In this study, we combined the paProtacL and paCas9 systems (Figure 8 ). We found that they were more effective in degrading Survivin levels than alone and that the combination promoted apoptosis and inhibited migration and proliferation of bladder cancer cells in vitro.…”
Section: Discussionmentioning
confidence: 99%
“… 51 The process involves introducing the components of the photocontrol system or cells containing the therapeutic gene into the human body and using light to induce the degradation of the target gene at the transcriptional and protein levels, thereby achieving a therapeutic effect. 52 , 53 In this study, we combined the paProtacL and paCas9 systems (Figure 8 ). We found that they were more effective in degrading Survivin levels than alone and that the combination promoted apoptosis and inhibited migration and proliferation of bladder cancer cells in vitro.…”
Section: Discussionmentioning
confidence: 99%